Novel use of covered stents to treat profound cyanosis in a hepatic vein exclusion Fontan - Sarosh P Batlivala; Makram R Ebeid (Wolters Kluwer Medknow Publications, 2019)
Fontan completion in patients with complex cardiac anatomy, and specifically heterotaxy syndrome, can present unique physiologic considerations. For example, existing venous connections may be "unmasked" after a cavopulmonary anastomosis operation. We present the case of a child with heterotaxy, dextrocardia, single-ventricle physiology, and anomalous hepatic venous drainage that resulted in profound shunting and cyanosis. We addressed the problem utilizing a novel strategy with a "fenestrated" covered stent.